Tracheal intubation with a camera embedded in the tube tip (Vivasight™). (5th November 2012) - Huitink, J. M.; Koopman, E. M.; Bouwman, R. A.; Craenen, A.; Verwoert, M.; Krage, R.; Visser, I. E.; Erwteman, M.; van, D.; Tijink, R.; Schauer, A.
Summary We studied tracheal intubation in manikins and patients with a camera embedded in the tip of the tracheal tube (Vivasight™). Four people in two teams and two individuals attempted intubation of a manikin through an i‐gel™ 10 times each. The tracheas of 12 patients with a Mallampati grade of 1 were intubated with a Vivasight tracheal tube through a Berman airway, passed over a Frova™ introducer. All 60 manikin intubations were successful, taking a mean (SD) time of 1.4 (0.5) s. The fastest intubation was performed in 0.5 s. All 12 participants' tracheas were successfully intubated in a median (IQR [range]) time of 90 (70–120 [50–210]) s. Seven participants complained of a sore throat, comparable with earlier findings for standard laryngoscopy and intubation: five mild; one moderate; and one severe. Tracheal intubation with the Vivasight through the i‐gel or Berman airway is an alternative to existing techniques, against which it should be compared in randomised controlled trials in human participants. It has potential as a fast airway rescue technique.